HASIL BELAJAR MATEMATIKA ANTARA SISWA YANG DIAJAR MENGGUNAKAN STRATEGI PEMECAHAN MASALAH MODEL POLYA DENGAN STRATEGI PEMBELAJARAN EKSPOSITORI - Septi Dariyatul Aini; Sri Indriati Hasanah (Prodi Pendidikan Matematika FKIP Universitas Madura, 2016)
According to Polya problem solving is defined as an attempt to find a way out of a difficulty in order to achieve an objective that is not so easily achieved immediately. While the expository teaching strategy is a learning strategy that emphasizes the process of delivery of content directly from a teacher to a group of students in order for students to master the subject matter optimally. Meanwhile, one of the materials studied in mathematics is the derivative function. From the above, efforts to be made to select a better learning strategies used in teaching mathematics is to compare learning outcomes between students who are taught math using Polya model problem-solving strategies with expository teaching strategies on the subject of the derivative function. Apparently after research showed that there was no comparison learning outcomes in math between students taught using Polya model problem-solving strategies is taught by using the expository teaching strategy.